The epistemological thought of a master. José Antonio Abreu Anselmi (Revista Electrónica REDINE, 2021)
In this article the guiding principles, values and action strategies used by the teacher José Antonio Abreu Alselmi, during his personal and professional life, are analyzed, discussed and justified. It is a study of a qualitative nature, supported by the biographical or life stories method. The article reconstructs and reveals the personal professional life of this distinguished Venezuelan, based on the analysis of personal testimonies of the teacher and other social actors, who accompnied him during his professional life and that allowed to reveal the thoughts, feelings and actions of the illustrious teacher, in search of the realization of a dream: the creation of a system of orchestra in Venezuela. It ends, specifying the ethical, moral and values principles ​​that the teacher modeled and exposed before Venezuela and the world, for the formation of a proactive citizen, through learning and teaching music
Keywords: guiding principles; values; qualitative research; life stories